Creative class in the borderlands? The case of commuting scholars in Poland - Łuczaj, Kamil; Leonowicz-Bukała, Iwona; Kurek-Ochmańska, Olga (Creativity Studies, 2022)
Richard Florida claims that members of the “creative class” move to cities, perceived as open and conducive to creative work – a phenomenon which Florida insists is a fundamental economic driver in the Western world. This includes academics and researchers and results in the transfer of knowledge and skills. As the concept of “creative class” was coined in the United States, we may pose the question if it is applicable in other social contexts. The geographical focus of the current paper is on the Polish borderlands. We investigate how international academic commuters, i.e. academics travelling to work in Poland from the neighbouring countries, contribute to the knowledge transfer, or more broadly, the “creative transfer”. This study, a part of a broader research project involving 100 foreign-born scholars working in Poland, uses a sub-sample of the 16 in-depth interviews with international commuting scholars (as opposed to those who presently live in Poland). The results show that most of the internationally commuting scholars come to Poland strictly to deliver teaching. Focused on this goal, they do not take part in social or cultural life in Poland. Although not earning enough money in their home countries, they do not want to move permanently to Poland. Instead, they use the opportunities given by living near the border. These practices make them more similar to regular economic migrants, rather than members of the “creative class”, although some traces of the “creative transfer” can be identified.